1983
DOI: 10.1139/v83-241
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mannich bases from electrochemically generated iminium salts in the presence of silyl enol ethers

Abstract: . Can. J. Chem. 61, 1379 (1983). The formation of Mannich bases from the reaction of silyl enol ethers with N-methyl-N-mesitylmethylcniminium salt, generated by the electrochemical oxidation of N,N-dimethylmesidine, was studied. Important factors influencing the reaction are: (a) the silyl enol ether must be nucleophilic enough to react with the iminium salt and, at the same time, must be more difficult to oxidize than the tertiary amine, (b) the product of the reaction must not be oxidized at the operating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In recent studies, we explored photochemical reactions of 1,2-diketone and silyl ketene acetals and showed that versatile C-C or C-O bond forming processes take place. On the basis of an analysis of the protoproducts presented previous study 1 , ground state/ excited state redox properties of 1,2-diketone electron acceptor [2][3] and silyl ketene acetal electron donor 4,5 , and results of photoreactions of monoketone analogs 4,[6][7][8] give plausible mechanistic pathways for 1,2-diketone with silyl ketene acetals (Scheme 1). Single electron transfer (SET)-promoted or direct [4+2] cycloaddition 1,9 , classical Paterno-Buchi [2+2] cycloaddition 1,4,10 , and sequential SET-desilylation processescompete for deactivation of the 1,2-dicarbonyl excited state by the silyl ketene acetals.…”
mentioning
confidence: 99%
“…In recent studies, we explored photochemical reactions of 1,2-diketone and silyl ketene acetals and showed that versatile C-C or C-O bond forming processes take place. On the basis of an analysis of the protoproducts presented previous study 1 , ground state/ excited state redox properties of 1,2-diketone electron acceptor [2][3] and silyl ketene acetal electron donor 4,5 , and results of photoreactions of monoketone analogs 4,[6][7][8] give plausible mechanistic pathways for 1,2-diketone with silyl ketene acetals (Scheme 1). Single electron transfer (SET)-promoted or direct [4+2] cycloaddition 1,9 , classical Paterno-Buchi [2+2] cycloaddition 1,4,10 , and sequential SET-desilylation processescompete for deactivation of the 1,2-dicarbonyl excited state by the silyl ketene acetals.…”
mentioning
confidence: 99%
“…The first paper of this series (1) described the synthesis of Mannich bases from the electrochemical oxidation of N,Ndimethylmesidine in the presence of silyl en01 ethers. It was noticed that the reaction depended upon the relative electrochemical oxidation potentials of the silyl en01 ether, the amine, and the product.…”
mentioning
confidence: 99%